High-selectivity magnetic covalent triazine organic polymer adsorbent as well as preparation method and application thereof

By synthesizing magnetic covalent triazine organic polymer adsorbent in aqueous solution, the problems of the existing magnetic porous organic polymers being low in separation efficiency in water treatment and the use of toxic solvents during preparation are solved, and high selectivity and Efficient heavy metal mercury ion adsorption removal, suitable for water quality monitoring and sewage treatment.

CN119219111AActive Publication Date: 2024-12-31HUANGGANG NORMAL UNIV
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411506824.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-28
Publication Date
2024-12-31
Estimated Expiration
2044-10-28

AI Technical Summary

Technical Problem

The existing magnetic porous organic polymer adsorbents have low separation efficiency in water treatment, complex operation, and require harsh conditions or toxic and harmful solvents during preparation, which limits their large-scale application.

Method used

The highly selective magnetic co-copy was synthesized by redox reaction by using monosodium thiocyanate, Fe3O4@SiO2 magnetic nanoparticles and 1,3,5-triazine-2,4,6-trithionone trisodium salt. Valid triazine organic polymer adsorbent realizes the efficient preparation of magnetic covalent triazine organic polymers in aqueous solution.

Benefits of technology

This method achieves high selectivity, easy separation, strong anti-interference ability, efficient adsorption and removal of heavy metal mercury ions, and the material can be reused. It is suitable for the rapid adsorption and desorption of mercury ions in water, reducing the cost of pollution control.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119219111A_ABST
    Figure CN119219111A_ABST
Patent Text Reader

Abstract

The invention discloses a high-selectivity magnetic covalent triazine organic polymer adsorbent as well as a preparation method and application thereof, and belongs to the technical field of magnetic solid adsorbent compositions. According to the invention, a high-selectivity magnetic covalent triazine organic polymer adsorbent is prepared through a green and mild oxidation-reduction reaction in a water-phase solution. The method has the advantages of low cost, simplicity, rapidness, mild reaction conditions, green and environment-friendly process, no consumption of harmful organic solvents and the like. The prepared adsorbent is rich in triazinyl and sulfydryl functional groups, is large in specific surface area, high in porosity and easy to magnetically separate, can realize high-selectivity adsorption of heavy metal mercury ions within a wider pH range, and is fast in adsorption kinetics and high in adsorption capacity. Besides, the high-selectivity magnetic covalent triazine organic polymer adsorbent can meet the requirements of multiple fields, has good applicability, and has wide application prospects in the fields of adsorption removal, extraction separation, enrichment, detection and the like of heavy metal mercury ions in water.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of magnetic solid adsorbent compositions, and in particular to a highly selective magnetic covalent triazine organic polymer adsorbent and a preparation method and application thereof. Background Art

[0002] Mercury (Hg), as a well-known highly toxic heavy metal element, is widely used in metallurgy, electrolysis, medicine, electronics and other fields. However, environmental pollution caused by mercury-related industries, especially water pollution, has become a serious global environmental problem. Mercury-contaminated water not only harms aquatic plants and animals, but also poses serious harm to humans and ecosystems through the food chain. The World Health Organization (WHO) stipulates that the maximum allowable concentration of mercury in drinking water is 1 μg L -1 The European Union (EU) requires that the mercury content in industrial wastewater should not exceed 50 μg L -1 The "Sanitary Standards for Drinking Water" and "Environmental Quality Standards for Surface Water" also set strict limits for the mercury content in drinking water and different types of surface water (0.05-1 μg L -1 ), therefore, how to efficiently remove excess mercury in water and accurately and sensitively measure trace mercury in water is crucial to ensuring water quality safety and environmental water quality testing.

[0003] Inductively coupled plasma mass spectrometry (ICP-MS) is a commonly used analytical instrument for detecting mercury in water. It has the advantages of high sensitivity and wide linearity. However, in actual sample analysis, it often faces challenges due to interference from the sample matrix and low concentration of the target substance. In order to improve detection sensitivity and reduce interference, before using instrumental analysis and detection, efficient solid adsorbents and solid-phase extraction (SPE) technology are usually used to achieve pre-separation of the sample matrix and pre-enrichment of the target element.

[0004] In recent years, new solid adsorption materials such as carbon-based materials, magnetic materials, mesoporous materials, metal organic framework materials, porous organic polymers, etc. have been continuously developed for water treatment and purification. Among them, porous organic polymers (POPs) are a kind of polymer network porous materials formed by covalently linking organic monomers composed of light-weight elements. Because of their advantages such as large specific surface area, high porosity, and adjustable structure, they are widely used in the adsorption of metal ions. However, due to their low density, POPs inevitably require cumbersome operations such as filtration and centrifugation when used for water treatment, which makes the solid-liquid two-phase separation time-consuming and inefficient, and the separation and recovery process of solid POPs adsorbents is cumbersome, which increases the complexity of the operation. By introducing magnetic nanomaterials into POPs, the magnetic POPs obtained can achieve rapid magnetic separation using an external magnetic field, thereby simplifying the separation operation, but the existing magnetic POPs mostly require harsh synthesis conditions or require the use of toxic and harmful organic solvents, expensive precious metal catalysts, etc. (Advances in magnetic porous organic frameworks for analysisand adsorption applications. Trac-Trends in Analytical Chemistry 2020, 132,116048.), which limits its large-scale application. Therefore, the development of a new green and mild method for preparing magnetic POPs is of great practical significance.

[0005] Trisodium thiocyanate is a low-cost, environmentally friendly heavy metal ion remover newly developed in recent years. It can react with sulfur-philic heavy metal ions such as Hg in water. 2+ , Pb 2+Plasma forms a stable compound and precipitates out, thereby achieving the purpose of removing heavy metal ions. However, trisodium thiocyanate is difficult to recycle and reuse after use as a homogeneous adsorbent. The solid adsorbent prepared by modifying thiocyanate or trisodium thiocyanate to some biomass solid materials can achieve efficient adsorption of metal ions, and the material can also be reused. For example, the Chinese invention patent with publication number CN109012604A provides a corn husk adsorbent material modified with thiocyanate, a preparation method and its application, which uses thiocyanate to modify corn husk adsorbent material to improve the adsorption rate of trace mercury ions. For another example, the Chinese invention patent with publication number CN110280219A discloses a preparation method of thiocyanate modified sunflower stem pith adsorbent, after pre-treating the sunflower stem pith of natural polymer, thiocyanate modified magnetic reed is used as an adsorbent to adsorb and separate gold, so that it has natural polymer characteristics and also has the selectivity of special active groups. However, all of the above preparation methods use toxic and harmful organic solvents or expensive organic monomers, which are not environmentally friendly and increase production costs and waste liquid treatment costs. In addition, these solid adsorbents require cumbersome steps such as filtration and centrifugation to recover the adsorbents during water treatment, resulting in low efficiency.

[0006] In summary, using low-cost raw materials and developing new green and mild methods to prepare adsorbents that are easy to separate and can be recycled multiple times has important practical significance for reducing the cost of heavy metal pollution control and achieving efficient separation and detection of heavy metal ions in water samples and sample matrices. Summary of the invention

[0007] In view of the above-mentioned defects of the prior art, in the first aspect of the present invention, a method for preparing a magnetic covalent triazine organic polymer adsorbent with high selectivity, which is low-cost, green, mild, efficient and convenient, is provided, comprising the following steps: (1) Prepare trithiocyanuric acid monosodium salt (TMS) solution; (2) A dispersion of Fe3O4@SiO2 magnetic nanoparticles with a core-shell structure and a solution of 1,3,5-triazine-2,4,6-trithioketone trisodium salt (TTS) were added to a solution of monosodium thiocyanate, and then a mixed solution of iodine and potassium iodide was added to carry out a redox reaction. After the reaction was completed, the product was recovered and purified to obtain a highly selective magnetic covalent triazine organic polymer adsorbent.

[0008] In the preparation method of the present invention, Fe3O4@SiO2 magnetic nanoparticles with a core-shell structure are used as the core, TMS and tri-TTS are used as functional monomers, and TMS and TTS are reduced by the oxidation of iodine to form polymers connected by disulfide bonds, thereby introducing covalent triazine organic polymers on the surface of the magnetic nanoparticles. Based on this principle, magnetic poly(trithiocyanuric acid) polymers (MPTAPs) are synthesized in an aqueous solution, i.e., highly selective magnetic covalent triazine organic polymer adsorbents.

[0009] Monosodium thiocyanate can be directly purchased as a commercial reagent, or it can be temporarily produced by the reaction of thiocyanate and sodium hydroxide. Considering that the cost of the finished product of monosodium thiocyanate is higher than that of thiocyanate and sodium hydroxide, under the premise of achieving the purpose of the present invention, it is suitable to prepare the monosodium thiocyanate solution by the reaction of thiocyanate and sodium hydroxide.

[0010] Preferably, in step (1), the monosodium thiocyanate solution is temporarily produced by the reaction of trithiocyanuric acid (TA) and sodium hydroxide in a solution environment, and the preparation method thereof comprises the following steps: Ultrasonic dispersion of thiocyanuric acid in water is performed to obtain a thiocyanuric acid dispersion liquid; sodium hydroxide aqueous solution is added to the thiocyanuric acid dispersion liquid, mixed and reacted to obtain a thiocyanuric acid monosodium salt solution.

[0011] Further preferably, the amount of thiocyanuric acid added is 1-2 mmol; the amount of water used is 50-100 mL; the concentration of the sodium hydroxide aqueous solution is 0.10-0.11 mol L -1 , the dosage is 10-20 mL.

[0012] Further preferably, the sodium hydroxide aqueous solution is added dropwise at a rate of 50-60 drops / min; the mixing stirring rate is 400-500 rpm; the reaction time is 2-3 h, and the reaction temperature is room temperature.

[0013] Preferably, in step (2), the dispersion of Fe3O4@SiO2 magnetic nanoparticles with a core-shell structure is prepared by adding 100-300 mg of Fe3O4@SiO2 magnetic nanoparticles with a core-shell structure to 25-30 mL of water and dispersing the dispersion by ultrasonication; the solution of 1,3,5-triazine-2,4,6-trithione trisodium salt is prepared by dissolving 0.5-1 mmol of 1,3,5-triazine-2,4,6-trithione trisodium salt in 25-30 mL of water; the mixed solution of iodine and potassium iodide is prepared by mixing 1 mmol of iodine with 5 mL of a 0.2-0.5 g mL -1 It is prepared by mixing an aqueous solution of potassium iodide.

[0014] The Fe3O4@SiO2 magnetic nanoparticles with a core-shell structure used in the steps can be directly obtained by using existing materials, commercial products, etc. or by homemade methods. The present invention is suitable for preparing the particles by coprecipitation method and sol-gel hydrolysis method. The coprecipitation method can obtain nanoparticle materials with uniform chemical composition through chemical reactions in a solution, which means that when preparing particles, metal ions can be evenly distributed during the precipitation process to ensure that each nanoparticle has a stable component ratio. The sol-gel hydrolysis method achieves highly uniform mixing of materials through liquid phase reactions, and can also improve the uniformity of nanoparticles. The sol-gel hydrolysis method can be carried out at a lower temperature, which helps to save energy and reduce costs.

[0015] Further preferably, the core-shell structured Fe3O4@SiO2 magnetic nanoparticles are prepared by a coprecipitation method and a sol-gel hydrolysis method, comprising the following steps: S1. Under an inert gas atmosphere, dissolve the chloride salt of Fe(III) and the chloride salt of Fe(II) in water, raise the temperature to 80-90°C and maintain for 50-60 min; then add concentrated ammonia water and continue to react at this temperature for 30-40 min; after the reaction is completed, cool to room temperature, recover and purify the product to obtain Fe3O4 magnetic nanoparticles; S2. Dispersing the Fe3O4 magnetic nanoparticles in a mixture of water and ethanol, adding concentrated ammonia and tetraethyl orthosilicate, forming a SiO2 layer on the surface of the Fe3O4 magnetic nanoparticles by hydrolysis of tetraethyl orthosilicate (TEOS), reacting at 25-30°C for 10-12 h, recovering and purifying the product, and obtaining Fe3O4@SiO2 magnetic nanoparticles with a core-shell structure.

[0016] In the preparation process of Fe3O4@SiO2 magnetic nanoparticles with core-shell structure, the chloride salts of Fe(III) and Fe(II) can be ferric chloride, ferrous chloride or their corresponding hydrates according to actual conditions.

[0017] Further preferably, in the S1, the amount of Fe(III) chloride salt is 20 mmol, the molar ratio of Fe(III) chloride salt to Fe(II) chloride salt is 2:1-1.1, and the amount of water is 100-150 mL; in the S2, the volume ratio of water to ethanol in the mixed solution is 1:3-4, the amount of the mixed solution is 150-200 mL, the amount of concentrated ammonia water is 2-2.5 mL, and the amount of tetraethyl orthosilicate is 2-2.5 mL.

[0018] Preferably, in the step (2), the addition of the raw materials and the redox reaction are carried out under stirring at a stirring rate of 400-500 rpm; when the mixed solution of iodine and potassium iodide is added, the temperature of the reaction system is 0-10°C to avoid volatilization of elemental iodine; the mixed solution of iodine and potassium iodide is added dropwise at a rate of 50-60 drops / min; after the addition of the mixed solution of iodine and potassium iodide is completed, the temperature is naturally raised to room temperature at room temperature.

[0019] Preferably, in step (2), the temperature of the redox reaction is room temperature and the reaction time is 10-12 h.

[0020] In the second aspect of the present invention, a highly selective magnetic covalent triazine organic polymer adsorbent is provided, which is easy to recycle and separate, has strong anti-interference ability, and has an efficient adsorption and removal effect on heavy metal mercury ions. The adsorbent is prepared by the method of the first aspect of the present invention.

[0021] According to the preparation method provided in the first aspect of the present invention, the structure of the prepared highly selective magnetic covalent triazine organic polymer adsorbent includes a magnetic Fe3O4 core, a SiO2 layer and a covalent triazine organic polymer layer based on thiocyanate, which are sequentially wrapped outside the Fe3O4 core. It has the characteristics of easy recovery and separation, strong anti-interference ability, and efficient adsorption and removal effect on heavy metal mercury ions.

[0022] In the third aspect of the present invention, there is provided an application of the highly selective magnetic covalent triazine organic polymer adsorbent of the second aspect of the present invention, specifically, its application as an adsorbent material for the adsorption, removal, extraction, separation, enrichment and detection of heavy metal mercury ions in water.

[0023] Based on the above technical scheme, the inventive concept of the present invention is to use monosodium thiocyanate and trisodium thiocyanate organic monomers as reducing agents, iodine as an oxidant, and a redox reaction under mild reaction conditions to synthesize polythiocyanate porous organic polymers on the surface of magnetic nanomaterials to prepare a magnetic covalent triazine organic polymer (MPTAPs) with high efficiency and high selectivity for adsorption and removal of heavy metal mercury ions. The preparation method provided by the present invention has the advantages of being green, mild, efficient, convenient, low cost, easy to prepare, and the material can be reused. The prepared material has the advantages of large specific surface area, wide pH range for adsorption, fast adsorption kinetics, high adsorption capacity, and easy dispersion and magnetic separation of the material. In addition, the material can achieve rapid adsorption and desorption of heavy metal mercury ions, and can tolerate interference from high concentrations of coexisting salts. It can achieve rapid extraction and separation under an external magnetic field, and can be used for efficient removal of mercury ions in acidic or neutral industrial wastewater, and can also be used for low concentrations of Hg 2+ It can achieve extraction enrichment and improve the sensitivity of detection, thereby realizing sensitive detection of mercury ions in environmental water samples and laboratory wastewater, and can provide heavy metal ion content information for water environment monitoring. It has good application prospects in the fields of sewage treatment and water quality analysis.

[0024] Compared with the prior art, the present invention has the following advantages and beneficial effects: The invention provides a method for preparing a highly selective magnetic covalent triazine organic polymer adsorbent, which has the advantages of high efficiency, convenience, greenness and mild reaction conditions.

[0025] The present invention provides a highly selective magnetic covalent triazine organic polymer adsorbent, which is composed of core-shell structured Fe3O4@SiO2 magnetic nanoparticles and a covalent triazine organic polymer layer based on thiocyanate. The adsorbent has the characteristics of easy recovery and separation, strong anti-interference ability, and efficient and highly selective adsorption and removal effect on heavy metal mercury ions.

[0026] The present invention provides an application of a highly selective magnetic covalent triazine organic polymer adsorbent, which can meet the use requirements in multiple fields, has good applicability, and has broad application prospects in multiple fields such as adsorption and removal, extraction and separation, enrichment and detection of heavy metal mercury ions in water. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 Schematic diagram of the synthesis of MPTAPs; Figure 2(a) and (b) are transmission electron microscope (TEM) images of Fe3O4@SiO2 magnetic nanoparticles with core-shell structure at different magnifications, and (c) and (d) are TEM images of MPTAPs at different magnifications. Figure 3 (a)-(d) are the infrared spectroscopy (IR), magnetic intensity, thermogravimetric and X-ray diffraction (XRD) characterization results of Fe3O4@SiO2 core-shell magnetic nanoparticles and MPTAPs respectively; Figure 4 The nitrogen adsorption / desorption isotherms and pore distribution diagrams of MPTAPs; Figure 5 Effect of pH on Hg adsorption by MPTAPs 2+ and the effects of common coexisting metal ions; Figure 6 (a) and (b) are the effects of adsorption time on Hg adsorption by MPTAPs. 2+ The influence of and the pseudo-second-order adsorption kinetics fitting curve; Figure 7 (a) and (b) are the effects of initial mercury ion concentration on the adsorption of Hg by MPTAPs. 2+ The influence of and the Langmuir adsorption isotherm fitting curve; Figure 8 (a)-(d) The effects of thiourea content, hydrochloric acid concentration, elution volume and elution time on the extraction of Hg from MPTAPs 2+ The impact of recovery rate.

[0028] Fig. 9 (a)-(c) The effects of sample volume, adsorption time, and adsorbent dosage on the extraction of Hg by MPTAPs 2+ The impact of the recovery rate; Fig.10 To investigate the reusability performance of MPTAPs. DETAILED DESCRIPTION

[0029] The present invention is further described below by way of examples, but the present invention is not limited to the scope of the examples. The experimental methods in the following examples without specifying specific conditions are carried out according to conventional methods and conditions, or selected according to the product specifications.

[0030] In the following examples, the core-shell structured Fe3O4@SiO2 magnetic nanoparticles were prepared by the following steps: S1. Under nitrogen protection, weigh 5.41 g FeCl3·6H2O and 1.99 g FeCl2·4H2O and place them in a 250 mL three-necked flask, add 100 mL high-purity water, start mechanical stirring to dissolve the iron salt, and then heat to 85 °C in a constant temperature water bath and mechanical stirring conditions and maintain for 1 h; then increase the nitrogen flow rate and stirring speed, add 20 mL concentrated ammonia water, the color of the mixed solution changes from orange to black, continue to stir at constant temperature for 30 min, then stop heating, cool to room temperature, stop mechanical stirring, remove nitrogen protection, and remove the supernatant from the obtained solid-liquid mixture by magnetic separation. The magnetic solid is washed with high-purity water and ethanol for 3-4 times each to obtain Fe3O4 magnetic nanoparticles, which are stored in 100 mL ethanol; S2. Add Fe3O4 magnetic nanoparticles to a mixed solution of 200 mL high-purity water and ethanol (1:3, v / v), disperse them evenly by ultrasonication, add 2 mL of concentrated ammonia water and 2 mL of TEOS under mechanical stirring, and stir the mixed solution in a constant temperature water bath at 30 °C for 12 h. After the reaction, wash the obtained solid material with high-purity water and ethanol for 3-4 times each, and dry it in a vacuum at 60 °C for 24 h to obtain Fe3O4@SiO2 magnetic nanoparticles with a core-shell structure.

[0031] Example 1 A method for preparing a highly selective magnetic covalent triazine organic polymer adsorbent, such as Figure 1 As shown, the steps are as follows: (1) Weigh 177 mg TA (i.e. 1 mmol) and ultrasonically disperse it in 60 mL high-purity water. Add it to a 250 mL three-necked flask, start mechanical stirring at 400 rpm, and then add 10 mL of 0.1 mol / L -1 Add sodium hydroxide aqueous solution to the TA solution and stir in a water bath at room temperature for 2 h to prepare a TMS solution; During the stirring reaction, 200 mg of Fe3O4@SiO2 magnetic nanoparticles with core-shell structure were weighed and placed in 25 mL of high-purity water for ultrasonic dispersion to obtain a dispersion of Fe3O4@SiO2 magnetic nanoparticles with core-shell structure; 243 mg (i.e. 1 mmol) of TTS was weighed and placed in 25 mL of high-purity water for ultrasonic dispersion to obtain a TTS solution; 508 mg (i.e. 2 mmol) of iodine was weighed and placed in 5 mL of 0.2 g mL -1 The potassium iodide solution is mixed to prepare a mixed solution of iodine and potassium iodide; (2) Add the dispersion of Fe3O4@SiO2 magnetic nanoparticles with core-shell structure and TTS solution to the prepared TMS solution while maintaining the aforementioned mechanical stirring rate. Then, add an appropriate amount of ice to the water bath to maintain the ice-water bath temperature at 0-10°C. Then, add a mixed solution of iodine element and potassium iodide at a rate of 60 drops / min. After the solution is added, no more ice is added to maintain the low temperature of 0-10°C. The water bath is not turned on for heating. The ice-water bath is allowed to naturally warm up to room temperature at room temperature. The reaction is stirred for 12 h at room temperature. After the reaction is completed, the crude product is washed with water 2-3 times and then washed with 0.1 mol L -1 The product was washed 3-4 times with a mixed solution of dilute hydrochloric acid aqueous solution and ethanol (1:1, v / v) as a detergent and then washed with water until neutral. The solid product was freeze-dried to obtain a highly selective magnetic covalent triazine organic polymer adsorbent (MPTAPs). The yield of MPTAPs was calculated to be approximately 93% by weighing it and combining the amount of TMS, TTS monomers and Fe3O4@SiO2 magnetic nanoparticles.

[0032] Example 2 This example studies the effect of the molar ratio of TA and TTS when preparing MPTAPs. The specific implementation scheme is as follows: The amount of TA was kept basically the same as that in Example 1 (i.e., 1 mmol TA, corresponding to about 1 mmol of TMS), the amount of TTS was changed to 2 mmol and 3 mmol, respectively, and the molar ratios of TMS and TTS were 1:2 and 1:3, respectively. The other preparation conditions remained the same as in Example 1, and the corresponding two MPTAPs were prepared.

[0033] The solid product yield was weighed and calculated. It was found that when the molar ratio of TMS to TTS was 1:2 and 1:3, the MPTAPs yields were 79% and 62%, respectively. Compared with the MPTAPs prepared in Example 1 (the molar ratio of TMS to TTS was 1:1 and the yield was 93%), the yield was significantly reduced.

[0034] The possible reason is that when the molar ratio of TMS to TTS is 1:1, the reaction between the two is more thorough, which is related to the structure of TMS and TTS. The TMS molecule contains a sodium sulfide salt site, i.e., the sulfur anion active site, while the TTS monomer molecule contains three sodium sulfide salt sites, i.e., the sulfur anion active sites. In the presence of zero-valent iodine, the iodine as an oxidant will cause the two negative divalent sulfur anions to be oxidized to produce negative monovalent disulfide bonds, thereby connecting two adjacent TMS or TTS containing sulfur anions to form disulfide bonds, and at the same time, the iodine is reduced to produce negative monovalent iodine anions. Since there are three sulfur anion active sites on the TTS molecule, two adjacent TTS can each consume one sulfur anion active site to form a set of disulfide bonds. By analogy, multiple TTS can be connected to each other to form a long polymer chain. Similarly, a sulfur anion active site on TMS can also be connected to the remaining sulfur anion active sites on TTS, thereby successfully connecting TMS and TTS to each other. According to the valence balance, 1 mmol of iodine can oxidize 2 mmol of sulfur anions. When TMS and TTS are both used in an amount of 1 mmol in Example 1, the total amount of sulfur anions is 4 mmol. If all sulfur anions undergo a thorough oxidation reaction to form disulfide bonds, the amount of iodine should be 2 mmol. Therefore, when the TMS and TTS reaction molar ratio is 1:1, the reaction is more thorough. If the TMS and TTS reaction molar ratios are 1:2 and 1:3, it means that TTS reaction sites are in excess. Under the condition that the amount of oxidant iodine remains unchanged, a part of TTS will not undergo a redox reaction to form a disulfide bond, resulting in an excess of monomers, and the generated MPTAPs are less and the yield is low.

[0035] In order to improve product yield and reduce cost and reagent consumption, the reaction molar ratio of TMS to TTS was fixed at 1:1 in the subsequent examples.

[0036] Example 3 This example studies the effect of the amount of Fe3O4@SiO2 magnetic nanoparticles with a core-shell structure when preparing MPTAPs. The specific implementation scheme is as follows: The amounts of TMS and TTS were kept basically the same as in Example 1 (i.e., 1 mmol TA produced 1 mmol TMS and 1 mmol TTS), and the amounts of Fe3O4@SiO2 magnetic nanoparticles with core-shell structure were changed to 100 mg and 300 mg, respectively. The other steps were consistent with Example 1, and the yield of the solid product was weighed and calculated, and the magnetic size of different products was compared.

[0037] When the dosage of Fe3O4@SiO2 magnetic nanoparticles with core-shell structure is 100 mg and 300 mg respectively, the MPTAPs yields are 86% and 95% respectively, and the yields are all around 90%. However, the less the magnetic core, the weaker the magnetic properties of the obtained product. When the dosage of Fe3O4@SiO2 magnetic nanoparticles with core-shell structure is 100 mg, the magnetic properties of the obtained product are significantly weakened. After MPTAPs are dispersed in water, the magnetic separation sedimentation time requires more than 10 min, and the magnetic separation time is significantly increased. When the magnetic core is increased to 300 mg, the obtained product has strong magnetic properties and fast magnetic separation, but the proportion of organic polymers contained in the unit mass of MPTAPs adsorbent is reduced, and the adsorption sites will be reduced. When the magnetic core is 200 mg in Example 1, the obtained product has strong magnetic properties, a faster magnetic separation speed, and a higher proportion of organic polymers and a stronger adsorption capacity than the product prepared when the magnetic core is 300 mg.

[0038] Therefore, the amount of Fe3O4@SiO2 magnetic nanoparticles with core-shell structure in the subsequent examples was fixed at 200 mg.

[0039] Example 4 In this example, various material properties of the prepared core-shell structured Fe3O4@SiO2 magnetic nanoparticles and the MPTAPs of Example 1 were characterized.

[0040] Firstly, TEM was used to characterize the core-shell structured Fe3O4@SiO2 magnetic nanoparticles and MPTAPs to study the structural characteristics of magnetic hydroxyazobenzene porous organic polymer adsorbents. The corresponding results are shown in Figure 2 shown.

[0041] from Figure 2 It can be seen that Fe3O4@SiO2 is a core-shell structure, while MPTAPs is a porous network structure with a large amount of low-contrast polymer coating on the outer layer, indicating that porous organic polymers have been successfully prepared and wrapped on the surface of Fe3O4@SiO2 with a core-shell structure.

[0042] The core-shell structure of Fe3O4@SiO2 and MPTAPs was characterized by Fourier transform infrared spectroscopy, vibrating sample magnetometer thermogravimetry and X-ray powder diffractometer. The corresponding results are shown in Figure 3 shown.

[0043] from Figure 3 (a) It can be seen that Fe3O4@SiO2 has Si-O (1092 cm -1 )、Fe-O(580 cm -1), indicating that the core-shell structure of Fe3O4@SiO2 magnetic nanoparticles has been successfully prepared. The characteristic absorption peaks of TA and Fe3O4@SiO2 appeared in the infrared spectrum of MPTAPs, including the C=N stretching vibration absorption peak on the triazine ring of TA (1450 cm -1 、1251 cm -1 and 829 cm -1 near), and Si-O on Fe3O4@SiO2 (1089 cm -1 )、Fe-O(582 cm -1 ) stretching vibration characteristic absorption peak, indicating that the magnetic covalent triazine organic polymer based on trithiocyanate has been successfully prepared.

[0044] Figure 3 (b) is the magnetic intensity characterization of core-shell Fe3O4@SiO2 magnetic nanoparticles and MPTAPs. The saturation magnetic intensities of the two are 49.6 and 28.4 emu·g, respectively. -1 The magnetic strength of MPTAPs is smaller than that of Fe3O4@SiO2, indicating that a large amount of organic polymer coating has been successfully coated on the surface of Fe3O4@SiO2. Although the magnetic strength is reduced, it is sufficient for magnetic solid phase extraction separation.

[0045] Figure 3 (c) is the thermogravimetric characterization diagram of Fe3O4@SiO2 magnetic nanoparticles with core-shell structure and MPTAPs. In the measured temperature range, the weight loss percentage of Fe3O4@SiO2 is about 5%, indicating that the magnetic nanoparticles have high thermal stability and are difficult to thermally decompose. However, the weight loss percentage of MPTAPs is relatively high, about 64%. The small weight loss of MPTAPs between 100-300 ℃ may be caused by the evaporation of volatile molecules, and the large weight loss between 300-800 ℃ may be caused by the thermal decomposition of the hydrocarbon organic polymer components on MPTAPs, decomposing into carbon dioxide and water. The thermogravimetric results show that MPTAPs were successfully prepared. Compared with Fe3O4@SiO2 magnetic nanoparticles with core-shell structure, the hydrocarbon organic polymer components on MPTAPs account for a higher proportion.

[0046] Depend on Figure 3(d) It can be seen that the core-shell structured Fe3O4@SiO2 magnetic nanoparticles and MPTAPs have 6 characteristic diffraction peaks with almost identical diffraction angles, which appear at 2θ of 29.95°, 35.41°, 43.13°, 54.04°, 57.12°, and 63.07°, respectively. These characteristic peaks are characteristic diffraction peaks of Fe3O4, indicating that the core structure of magnetic Fe3O4 has not changed during the synthesis of MPTAPs. No additional XRD peaks were detected in MPTAPs, indicating that the organic polymer network outside MPTAPs belongs to an amorphous polymer.

[0047] In order to further verify the porosity of MPTAPs, N2 adsorption / desorption experiments were also carried out, and the corresponding results are shown in Figure 4 shown. Figure 4 The adsorption / desorption isotherms of MPTAPs show a hysteresis loop in the relative pressure range of 0.70-0.95, indicating that mesopores and macropores coexist in MPTAPs. The results of N2 adsorption / desorption experiments show that the pore volume and BET surface area of ​​MPTAPs are 0.63 cm 3 ·g -1 and 124 m 2 ·g -1 These values ​​are much higher than the pore volume and BET surface area (0.17 cm 3 ·g -1 and 35 m 2 ·g -1 ), which also shows that porous organic polymers have been successfully prepared on the surface of Fe3O4@SiO2 magnetic nanoparticles with core-shell structure.

[0048] Example 5 This example studies the adsorption performance of the MPTAPs prepared in Example 1 on heavy metal ions in application.

[0049] The effects of the MPTAPs prepared in Example 1 on eight heavy metal ions (Cd 2+ 、Co 2+ Cr 3 + , Cu 2+ , Hg 2+ 、Ni 2+ , Pb 2+ and Zn 2+ ) The adsorption performance of the mixed solution, the corresponding results are as follows Figure 5 (a) shows that MPTAPs have a significant effect on Hg 2+The adsorption rates of Hg and Mg were all higher than 90%, while the adsorption rates of the other seven metal ions were significantly lower. This result shows that MPTAPs can effectively adsorb Hg in a wide pH range (even in an acidic environment of pH = 2-3). 2+ The high selective adsorption capacity of MPTAPs for Hg in a wide pH environment (acidic or neutral solution) 2+ The applicability of MPTAPs for the selective separation of Hg 2+ The reason for the high selectivity may be that the thiol groups in MPTAPs bind to Hg 2+ This is related to the strong binding ability of Hg, which can be explained by Pearson's soft and hard acid-base theory: soft ligands, such as -SH, can easily bind to Hg 2+ Instead of forming complexes with boundary acids (such as Pb 2+ ) or hard acid (such as Co 2+ ). In addition, from Figure 5 (a) It can be seen that MPTAPs have a great influence on Cu 2+ and Pb 2+ The adsorption rate of Cu increased with the increase of pH and reached adsorption equilibrium at pH 6. 2+ and Pb 2+ pH dependence trend of MPTAPs on Hg 2+ The wide pH adaptability of HgS results in huge adsorption differences. This difference is related to the chelation constants of different metal ions with sulfur, because the Ksp of HgS remains stable at different pH levels (4×10 -53 ), while the Ksp of CuS and PbS are easily affected by acidic environment. Cu (6×10 -36 ) and Ksp PbS (1×10 -28 ) values ​​are relatively high, but in an acidic environment they will decrease to 6×10 -15 and 1×10 -6 Under strong acidic conditions (pH = 2-3), Hg 2+ The strong adsorption between MPTAPs and thiol groups enables the removal of Hg from industrial acidic wastewater. 2+ , which is very beneficial for controlling mercury pollution.

[0050] In order to further study the effects of MPTAPs on Cu 2+ and Pb 2+ The potential adsorption of Hg at pH 6 was 2+ In this case, MPTAPs were used to treat Cu 2+ and Pb 2+ Adsorption experiment. Figure 5 (b) shows that when Cu 2+ and Pb 2+ Ions and Hg 2+ When ions coexist, Hg 2+ ions can be completely adsorbed by MPTAPs, while Cu 2+ and Pb 2+ The adsorption rate of MPTAPs on Cu 2+ and Pb 2+ However, in the absence of Hg 2+ ions, MPTAPs for Cu 2+ The adsorption rate of Pb 2+ The adsorption rate of MPTAPs was 87.4%, indicating that 2+ The solution of ions has the effect of removing Cu 2+ and Pb 2+ Therefore, MPTAPs adsorbent can 2+ Treatment of Cu-containing 2+ and Pb 2+ Wastewater containing Cu 2+ and Pb 2+ Industrial wastewater (pH of the solution was pre-adjusted to 6) was mixed with 10 mg of MPTAPs to conduct an adsorption feasibility test. The results showed that the material 2+ and Pb 2+ The adsorption rate of MPTAP exceeded 85%, which verified that MPTAP can 2+ Removal of Cu from wastewater 2+ and Pb 2+ feasibility.

[0051] The above adsorption experiments confirmed that MPTAPs contained a large number of thiol groups, and also verified from the side that the Fe3O4@SiO2 surface was successfully modified with trithiocyanate-based covalent triazine organic polymers. It is worth noting that MPTAPs has a wide pH range for Hg 2+ Ions have high adsorption selectivity, which is beneficial for Hg 2+ Selective separation of ions. Considering that the pH value of daily water is close to neutral and metal ions are easily hydrolyzed under alkaline conditions, subsequent adsorption studies were carried out at pH = 6.

[0052] In order to further explore the effects of MPTAPs on Hg 2+ The adsorption capacity of the fixed MPTAPs was 10 mg and the initial Hg 2 +Under the condition of 100 mg L-1 concentration, the adsorption of Hg by MPTAPs was carried out by changing the adsorption time to 1 min, 3 min, 5 min, 7 min, 10 min, 15 min and 20 min. 2+ Adsorption kinetics experiments Figure 6 (a). Hg at different adsorption times 2+ Adsorption amount on MPTAPs (Qt, mg g -1 ) increased rapidly in the first 5 min, and then reached adsorption equilibrium in about 10 min. This indicates that MPTAPs can 2+ The adsorption process is very fast, which can be attributed to the presence of abundant highly active thiol binding sites and hierarchical pores (micropores and macropores) on MPTAPs, which are conducive to the rapid adsorption and removal of Hg. 2+ In order to achieve efficient adsorption, in subsequent experiments, MPTAPs and Hg 2+ The adsorption contact time was fixed at 10 min. Figure 6 The adsorption data of MPTAPs to Hg 2+ The maximum adsorption capacity is 209 mg g -1 , indicating that MPTAPs have a significant effect on Hg 2+ After further data fitting, it was found that MPTAPs has a strong adsorption capacity for Hg 2+ The adsorption of Hg by MPTAPs conforms to the pseudo-second-order adsorption kinetic model. 2+ The adsorption of Hg by MPTAPs under acidic conditions (pH = 2) was also studied. 2+ The adsorption kinetics of MPTAPs on Hg 2+ The maximum adsorption capacity was 187 mg g -1 , and the adsorption equilibrium was reached in about 10 min. This result verifies that Hg 2+ The stability of the sulfur chelation constant indicates that MPTAPs are effective in removing Hg from industrial acidic wastewater. 2+ The MPTAPs have great application potential for Hg ions. The actual industrial acidic wastewater containing mercury was used for verification and a satisfactory mercury removal rate (92%) was obtained, confirming the effectiveness of MPTAPs in removing Hg 2+ The feasibility of ions.

[0053] In order to further study the adsorption mechanism, 10 mg MPTAPs and Hg 2+ The solutions were mixed for 10 min and the initial concentrations (5-100 mg L -1 Hg 2+) on adsorption. Figure 7 As shown in (a), Hg 2+ The adsorption amount increased with the initial concentration from 5 mg L -1 Increase to 50 mg L -1 and then increased to 60-100 mg L -1 After calculation, it was found that the MPTAPs had a 2+ The maximum adsorption capacity was 211 mg g -1 After further data fitting, it was found that MPTAPs 2+ The adsorption of Hg 2+ The adsorption belongs to single layer adsorption.

[0054] Example 6 This example uses actual industrial acidic wastewater to verify and study the extraction of Hg by MPTAPs in the application. 2+ feasibility and optimal extraction conditions.

[0055] According to Example 5, MPTAPs adsorbs Hg 2+ The pH range is 2-8. Considering that the pH value of domestic water is close to neutral, and in order to reduce the hydrolysis behavior of metal ions in an alkaline environment, MPTAPs extraction of Hg was performed at pH 6. 2+ The specific method is to use Hg at pH = 6. 2+ A certain amount of MPTAPs was added to the solution and shaken on a shaker for 10 min to make Hg 2 + Adsorbed on MPTAPs, then magnetically separated, the supernatant was taken out to measure Hg 2+ content, and then adsorbed Hg 2+ A certain volume of acidic thiourea solution was added to the MPTAPs material as an eluent and vortexed for 10 min to desorb Hg 2+ After magnetic separation, the supernatant was collected to measure Hg 2+ Content. Figure 8 (a) It can be seen that when the HCl concentration in the acidic thiourea solution is set to 1 mol L -1 , and when the thiourea content exceeds 0.2%, Hg 2+ The ions can be quantitatively eluted. In order to ensure a high elution rate, the thiourea content was set to 0.4% in subsequent studies. The effect of HCl concentration in the acidic thiourea solution was then investigated. Figure 8 (b) It can be seen that when the HCl concentration in the acidic thiourea solution exceeds 0.4 mol L -1 When Hg 2+The recovery rate was above 90%. To ensure complete elution, the subsequent eluent composition was set to 0.5 mol L containing 0.4% thiourea. -1 HCl solution. Other elution conditions, including elution volume and elution time, were then studied. Figure 8 (c) and Figure 8 (d) The optimal elution condition was 0.4 mL of 0.5 mol L-1 containing 0.4% thiourea. -1 The HCl solution was vortexed and eluted for 3 min.

[0056] Based on the above optimized conditions, the effects of sample solution volume, extraction adsorption time, and material dosage on the extraction of Hg by MPTAPs were studied. 2+ The recovery rate of Fig. 9 According to the data results in the test solution volume of 100 mL, the extraction adsorption time of 10 min, and the material dosage of 10 mg, Hg 2+ It can be quantitatively adsorbed and quantitatively eluted by quantitative MPTAPs. Dividing the 100 mL sample volume by the 0.4 mL elution volume, the theoretical enrichment factor is calculated to be 250 times. This shows that MPTAPs can be used to quantitatively detect Hg in large volume water samples. 2+ Extraction and separation of even trace amounts of Hg 2+ , after elution with a small volume of eluent, Hg 2+ The concentration of trace Hg 2+ Ultra-sensitive detection.

[0057] Example 7 This example studies the use of MPTAPs to extract Hg 2+ The ability to tolerate interference from coexisting salts and its reusability.

[0058] In the presence of 10 ng Hg 2+ Different concentrations of various common ions (such as K + 、Na + , Fe 3+ 、Al 3+ and Cl - Subsequently, the extraction process was carried out using the previously optimized magnetic solid phase extraction (MSPE) conditions to evaluate the effects of different levels of these common coexisting ions on the extraction of Hg from MPTAPs. 2+ The results are shown in Table 1.

[0059] Table 1: Trace Hg extracted by MPTAPs 2+ Maximum tolerable concentration of coexisting interfering ions

[0060] From the experimental results in Table 1, it is found that the highest tolerable concentration of these coexisting ions can reach 12000 mgL -1 The presence of these high concentrations of coexisting ions has an important influence on the extraction of Hg by MPTAPs. 2+ In addition, the maximum tolerable concentrations of these coexisting ions are lower than the target Hg 2+ The concentrations of ions were all several thousand times higher, which highlights the strong anti-interference ability of the prepared MPTAPs.

[0061] In addition, the regeneration and reuse times of the MPTAPs adsorbent were investigated. After one round of extraction, the MPTAPs adsorbent was washed with 0.4 mL of 0.4% thiourea in 0.5 mol L -1 HCl solution will remove the small amount of Hg remaining on the MPTAPs 2+ After elution, the selective adsorption sites were fully exposed, washed with high-purity water until neutral, and then treated with 0.1 mol L -1 After activation with ammonium acetate solution, MPTAPs can be regenerated and the adsorption and desorption steps can be repeated. Fig.10 As shown in the figure, MPTAPs were used repeatedly in the order of adsorption, desorption, cleaning, and activation. The results showed that even after being reused 10 times, MPTAPs had no significant effect on Hg 2+ The recovery rate did not decrease significantly, indicating that MPTAPs have good stability and regeneration performance.

[0062] Example 8 This example studies the effect of MPTAPs on Hg 2+ separation, enrichment and detection.

[0063] The MPTAPs prepared in Example 1 were used to establish MSPE-ICP-MS detection of Hg by coupling MSPE with ICP-MS. 2+ Under the extraction conditions optimized in Example 6, the analytical performance of the new MSPE-ICP-MS method based on MPTAPs proposed in the present invention was investigated, and the results are shown in Table 2.

[0064] Table 2: Analytical performance of the MSPE-ICP-MS method based on MPTAPs

[0065] This new method is used to 2+ The detection limits were 0.61 ng L -1 The linear range is 2-3000 ng L -1The relative standard deviations within the batch (n=7) and between batches (n=5) were 5.7% and 8.5%, respectively, and the actual enrichment factor was 232 times. 2+ The detection limit (73 ng L -1 ), after MSPE extraction, the detection limit decreased significantly and the detection sensitivity was significantly improved.

[0066] By analyzing the Hg in the standard water sample (pre-diluted 10 times) of GSB 07-3173-2014 "Water Quality Mercury Standard Sample" 2+ , verify the accuracy of the MSPE-ICP-MS method, and the results are shown in Table 3.

[0067] Table 3: Hg in reference materials 2+ Content determination results (n=3)

[0068] The results showed that the measured values ​​obtained by the MSPE-ICP-MS method were very close to the standard values, indicating that this MPTAPs-based MSPE-ICP-MS method has high accuracy.

[0069] Under the optimal conditions, the established method was applied to the determination of Hg in the Huanggang section of the Yangtze River, Yiai Lake water, laboratory tap water, and laboratory wastewater. 2+ The results are shown in Table 4.

[0070] Table 4: Detection of Hg in actual water samples using MSPE-ICP-MS 2+ Content (n=3)

[0071] In the table, “ / ” means there is no data available for detection.

[0072] From the table above, we can see that Hg 2+ Not detected, Hg in river water, lake water, laboratory wastewater 2+ There are different degrees of detection, and the spike recovery rate is between 88.2% and 111%. This shows that the method of the present invention has good anti-interference ability and can be used for trace Hg in actual water samples. 2+ separation, enrichment and detection.

[0073] The above research results show that compared with simple porous organic polymers, the MPTAPs prepared by the present invention not only have the advantages of high porosity and rich adsorption sites of porous organic polymers, but also can achieve rapid separation under an external magnetic field, avoiding tedious phase separation operations such as centrifugation and filtration, improving separation and enrichment efficiency, and overcoming the disadvantage that porous organic polymers are difficult to separate quickly, making the application of this new porous material more convenient and efficient.

[0074] Compared with other solid adsorbents based on thiocyanate, the preparation method of the MPTAPs prepared by the present invention has the advantages of being green, mild, efficient, convenient, low-cost, easy to prepare, easy to separate and recover, and the material can be reused many times. The prepared new adsorbent can highly selectively adsorb heavy metal ions Hg in water within a wide pH range. 2+ , even in acidic wastewater, Hg 2+ It has high adsorption capacity and fast adsorption kinetics, and can achieve high concentration of heavy metal ions Hg in sewage with different pH values. 2+ Highly efficient and selective rapid removal of Hg-free 2+ Neutral Cu 2+ , Pb 2+ The prepared magnetic adsorbent also showed good adsorption and removal effect. These experiments fully proved that MPTAPs has good application prospects in heavy metal wastewater treatment.

[0075] The MPTAPs prepared by the present invention can also achieve low concentration of heavy metal ions Hg in complex water samples. 2+ Extraction of trace Hg 2+ The separation of complex sample matrices can reduce the influence of sample matrix on the test results when combined with modern instruments for detection. By optimizing the adsorption and desorption conditions, trace Hg 2+ This magnetic solid phase extraction technology based on magnetic covalent triazine organic polymer adsorbent is a good choice for the enrichment of trace Hg 2+ It provides new ideas for detection.

[0076] The preferred specific embodiments of the present invention are described in detail above. It should be understood that a person skilled in the art can make many modifications and changes based on the concept of the present invention without creative work. Therefore, any technical solution that can be obtained by a person skilled in the art through logical analysis, reasoning or limited experiments based on the concept of the present invention on the basis of the prior art should be within the scope of protection determined by the claims.

Claims

1. A method for preparing a highly selective magnetic covalent triazine organic polymer adsorbent, characterized in that: The steps include: (1) Prepare monosodium thiocyanate solution; (2) A dispersion of Fe3O4@SiO2 magnetic nanoparticles with a core-shell structure and a solution of 1,3,5-triazine-2,4,6-trithione trisodium salt are added to a solution of monosodium thiocyanate, and then a mixed solution of iodine and potassium iodide is added to carry out a redox reaction. After the reaction is completed, the product is recovered and purified to obtain a highly selective magnetic covalent triazine organic polymer adsorbent.

2. The method for preparing a highly selective magnetic covalent triazine organic polymer adsorbent according to claim 1, characterized in that: In the step (1), the monosodium thiocyanate solution is temporarily produced by the reaction of thiocyanate with sodium hydroxide in a solution environment, and the preparation method thereof comprises the following steps: Ultrasonic dispersion of thiocyanuric acid in water is performed to obtain a thiocyanuric acid dispersion liquid; sodium hydroxide aqueous solution is added to the thiocyanuric acid dispersion liquid, mixed and reacted to obtain a thiocyanuric acid monosodium salt solution.

3. The method for preparing a highly selective magnetic covalent triazine organic polymer adsorbent according to claim 2, characterized in that: The amount of thiocyanuric acid added is 1-2 mmol; the amount of water used is 50-100 mL; the concentration of the sodium hydroxide aqueous solution is 0.10-0.11 mol L -1 , the dosage is 10-20 mL; the sodium hydroxide aqueous solution is added dropwise at a rate of 50-60 drops / min; the mixing stirring rate is 400-500 rpm; the reaction time is 2-3 h, and the reaction temperature is room temperature.

4. The method for preparing a highly selective magnetic covalent triazine organic polymer adsorbent according to claim 1, characterized in that: In the step (2), the dispersion of Fe3O4@SiO2 magnetic nanoparticles with a core-shell structure is prepared by adding 100-300 mg of Fe3O4@SiO2 magnetic nanoparticles with a core-shell structure to 25-30 mL of water and dispersing the mixture by ultrasonication; the 1,3,5-triazine-2,4,6-trithione trisodium salt solution is prepared by dissolving 1-3 mmol of 1,3,5-triazine-2,4,6-trithione trisodium salt in 25-30 mL of water; the mixed solution of iodine and potassium iodide is prepared by mixing 1 mmol of iodine with 5 mL of a 0.2-0.5 g mL -1 It is prepared by mixing an aqueous solution of potassium iodide.

5. The method for preparing a highly selective magnetic covalent triazine organic polymer adsorbent according to claim 4, characterized in that: The core-shell structured Fe3O4@SiO2 magnetic nanoparticles are prepared by coprecipitation and sol-gel hydrolysis, comprising the following steps: S1. Under an inert gas atmosphere, dissolve the chloride salt of Fe(III) and the chloride salt of Fe(II) in water, raise the temperature to 80-90°C and maintain for 50-60 min; then add concentrated ammonia water and continue the reaction at this temperature for 30-40 min; after the reaction is completed, cool to room temperature, recover and purify the product to obtain Fe3O4 magnetic nanoparticles; S2. Dispersing the Fe3O4 magnetic nanoparticles in a mixture of water and ethanol, adding concentrated ammonia water and tetraethyl orthosilicate, forming a SiO2 layer on the surface of the Fe3O4 magnetic nanoparticles by hydrolysis of tetraethyl orthosilicate, reacting at 25-30°C for 10-12h, recovering and purifying the product, and obtaining Fe3O4@SiO2 magnetic nanoparticles with a core-shell structure.

6. The method for preparing a highly selective magnetic covalent triazine organic polymer adsorbent according to claim 5, characterized in that: In the S1, the amount of Fe(III) chloride salt is 20 mmol, the molar ratio of Fe(III) chloride salt to Fe(II) chloride salt is 2:1-1.1, and the amount of water is 100-150 mL; in the S2, the volume ratio of water to ethanol in the mixed solution is 1:3-4, the amount of the mixed solution is 150-200 mL, the amount of concentrated ammonia water is 2-2.5 mL, and the amount of tetraethyl orthosilicate is 2-2.5 mL.

7. The method for preparing a highly selective magnetic covalent triazine organic polymer adsorbent according to claim 1, characterized in that: In the step (2), the addition of the raw materials and the redox reaction are carried out in a stirring environment at a stirring rate of 400-500 rpm; when the mixed solution of iodine and potassium iodide is added, the temperature of the reaction system is 0-10°C to avoid volatilization of the iodine element; the mixed solution of iodine and potassium iodide is added dropwise at a rate of 50-60 drops / min; after the addition of the mixed solution of iodine and potassium iodide is completed, the temperature is naturally raised to room temperature at room temperature.

8. The method for preparing a highly selective magnetic covalent triazine organic polymer adsorbent according to claim 1, characterized in that: In the step (2), the temperature of the redox reaction is room temperature and the reaction time is 10-12 h.

9. A highly selective magnetic covalent triazine organic polymer adsorbent, characterized in that: The method is prepared according to any one of claims 1 to 8.

10. A use of the highly selective magnetic covalent triazine organic polymer adsorbent as claimed in claim 9, characterized in that: It is used as an adsorption material for the adsorption, removal, extraction, separation, enrichment and detection of heavy metal mercury ions in water.

Citation Information

Patent Citations

  • Corn husk adsorbent material modified with thiocyanuric acid, and preparation method and application thereof

    CN109012604A

  • Preparation method of trithiocyanuric acid modified sunflower stem pith adsorbent

    CN110280219A

  • Gold ion imprinting magnetic adsorbent as well as preparation method and application thereof

    CN107376876A

  • Supramolecular polymer magnetic heavy metal adsorbent and preparation method and application thereof

    CN110052255A

  • Trithiocyanuric chloride high polymer material as well as preparation method and application thereof

    CN115286795A